2016
DOI: 10.12938/bmfh.2015-022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic and prebiotic fermented milk on skin and intestinal conditions in healthy young female students

Abstract: Although persistent constipation is considered to be associated with skin problems, the supporting evidence is limited. Hence, this study investigated the effects of probiotic and prebiotic fermented milk on skin and intestinal conditions in an open-label trial. Among the 101 Japanese healthy young female students that participated, the 81 subjects in the intake group consumed a bottle of probiotic and prebiotic fermented milk containing Bifidobacterium breve strain Yakult and galactooligosaccharides daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 19 publications
2
49
0
3
Order By: Relevance
“…There is a rather small number of studies on healthy subjects to show a beneficial effect of probiotics on skin health (Figure 1) [18,61,[90][91][92]. In one such study, when the L. lactis strain; H61 was supplemented on middle-aged women, daily for eight weeks, an improvement on skin elasticity and body characteristics were observed (e.g., skin appeared more hydrated and the hair follicles had improved) [92].…”
Section: Probiotics and Prebiotics On Skin Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a rather small number of studies on healthy subjects to show a beneficial effect of probiotics on skin health (Figure 1) [18,61,[90][91][92]. In one such study, when the L. lactis strain; H61 was supplemented on middle-aged women, daily for eight weeks, an improvement on skin elasticity and body characteristics were observed (e.g., skin appeared more hydrated and the hair follicles had improved) [92].…”
Section: Probiotics and Prebiotics On Skin Healthmentioning
confidence: 99%
“…Most common species of probiotics belong in the families of Lactobacillus, Bifidobacterium and Streptococcus [9] with the first two families being mostly used in studies related to human health [10]. As these microorganisms are naturally found in the gut microbiota, most studies are focused on their effects in the context of the natural function in the gut and as preventive or therapeutic agents against disease development [11][12][13][14][15][16][17][18]. To this end, probiotics have been used for the study and treatment of intestinal diseases such as gastroenteritis [19], intestinal hyperpermeability [20], urinary tract infection [21], intestinal dysbiosis [22], irritable bowel syndrome [23], Crohn's disease [24], colon cancer [25,26], ulcerative colitis [27,28] and peptic ulcer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Miyazaki, Masuoka, Kano, and Iizuka (2014) suggest that intake of certain probiotics and/or prebiotics (nondigestible food ingredients that stimulate the growth of beneficial bacteria in the colon) improves intestinal microbial balance, and thereby reduces phenol production, which is associated with maintenance of good skin condition. Mori et al (2016) reported that intake of fermented milk containing B. breve strain Yakult plus galactooligosaccharides prevented dryness in human skin via beneficial effects on intestinal conditions that stimulate defecation and decrease phenol production.…”
Section: Other Possible Mechanismsmentioning
confidence: 99%
“…Разработаны пробиотики на основе монокультур, поликомпонентные препараты, пробиотики на основе нетипичных для нормальной микрофлоры микроорганиз-мов, симбиотики (комбинации про-и пребио-тиков), препараты на основе рекомбинантных генно-инженерных штаммов, мультибиотики. Доказано, что пробиотики обладают способно-стью уменьшать популяцию вредных кишечных бактерий и улучшать состояние кожи [80][81][82][83][84][85][86]. Недавние исследования показали, что проби-отики могут улучшить течение АД, заживление ран и шрамов и способствуют омоложению кожи.…”
Section: изменения микробиоты при заболеваниях кожиunclassified
“…Все больше данных свидетельствуют о том, что потребление потенциально пробиотиче-ских молочнокислых бактерий может улучшить здоровье кожи [8,[90][91][92][93]. Предполагают, что этому способствует ограничение неблагопри-ятной кишечной бактериальной популяции, производящей фенолы, которые могут нару-шать состояние кожи [8,91].…”
Section: изменения микробиоты при заболеваниях кожиunclassified